The Kenosis of Jesus Christ: Model of the Christian Life According To Philippians 2:5-11 - Ramarolahy Patricia Josette; Robijaona Rahelivololoniaina Baholy (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
In the ancient city of Philippi, resonant with echoes of a bygone prosperity, the apostle Paul wove an indelible narrative in his epistle to the Philippians. Penned during his Roman imprisonment, this literary masterpiece, nestled within the realm of captivity epistles, expresses gratitude to a church intimately entwined with Paul's challenges. At its core lies a profound theme—the "Kenosis of Jesus Christ," unraveling divine humility as expounded in Philippians 2:5-11. This theological journey delves into diverse interpretations by researchers, spanning epochs from the Church Fathers to contemporary theologians. While the Church Fathers grapple with the dual nature of Jesus, reformers and modern theologians provide nuanced perspectives, revealing the enduring relevance of kenosis. The ramifications of kenosis on Malagasy life manifest in humanitarian salvation, exemplified in the voluntary abasement and subsequent exaltation of Jesus Christ outlined in Philippians 2:5-11. This transformative power extends beyond theological discourse, influencing progress, national reconciliation, and ecclesiastical renewal in the daily life of Madagascar. Examining the compatibility of kenosis with Madagascar's development, we discern its potential as both a tool and an obstacle. As an effective tool, kenosis aligns with the true preaching of the Gospel and the lived experience of humility, fostering a trajectory toward societal flourishing. However, as an obstacle, it is manifested in the tolerance of injustice, and conflicting with the current societal situation. Kenosis emerges as a profound concept in Christian theology, inviting believers to embody the humility exemplified by Christ. The theological journey traverses diverse interpretations, illuminating the richness and complexity of this motif. In the context of Madagascar, kenosis catalyzes positive shifts in daily life, national reconciliation, and ecclesiastical renewal. This paradigm offers a transformative pathway for countries in progress, transcending economic metrics to embrace societal flourishing. The compatibility of kenosis with Madagascar's development calls for a recalibration of societal values, blending true Gospel preaching and humility to counter contemporary challenges and embrace the profound meaning of kenosis.